Numerical simulation and analysis of CO diffusion and migration law of explosion-proof vehicle exhaust in confined underground space - TAN Bo; WANG Shanqi; LU Hao; JIA Zixuan; GAO Saiyi; JIANG Haibin (矿业科学学报, 2025)
With the construction and implementation of intelligent mine, explosion-proof diesel vehicles have been widely used for underground transportation. Because the coal mine roadway space is relatively small and closed, the gas flow condition is poor, and the CO generated in the operation process is not easy to discharge, which poses a potential threat to the operation facilities and staff. To this end, Fluent software was used in this paper to simulate the situation of explosion-proof diesel vehicles under idle start condition, and the law of CO diffusion and migration in the exhaust gas of explosion-proof diesel vehicles under the multi-factor conditions of air volume, wind direction and temperature was explored. The results show that when the explosion-proof diesel vehicle is subjected to tailwind in the driving direction, CO is discharged in the horizontal direction and has the trend of lateral migration when the air volume is small, and the migration range of CO is significantly reduced with the increase of the wind speed, and a small amount of CO has the trend of downward migration. In case of headwind, CO migrates backward and upward when the wind speed is low, and CO migrates laterally when the wind speed increases. When the temperature increases, the migration range of CO increases and the concentration of CO increases.